การบริหารจัดการทรัพยากรสารสนเทศดิจิทัลอันเป็นลิขสิทธิ์ของสถาบันอุดมศึกษาไทย - ติณะมาศ, ศศิธร; ลอยฟ้า, สมาน (บรรณศาสตร์ มศว, 2014)
งานวิจัยครั้งนี้ มีวัตถุประสงค์เพื่อศึกษาสภาพ ปัญหาและความต้องการในการบริหารจัดการทรัพยากรสารสนเทศดิจิทัลอันเป็นลิขสิทธิ์ของสถาบันอุดมศึกษาไทย โดยเก็บข้อมูลจากการสัมภาษณ์ผู้บริหารระดับสูง จำนวน 7 คน ผู้ปฏิบัติงานในหน่วยงานที่เกี่ยวข้อง จำนวน 16 คน ผลการวิจัยด้านสภาพ พบว่า 1) ยังไม่มีการกำหนดนโยบายและกลยุทธ์โดยตรงเกี่ยวกับการบริหารจัดการทรัพยากรสารสนเทศดิจิทัล 2) ห้องสมุดเป็นหน่วยงานที่รับผิดชอบโดยตรง ทั้งการผลิต เผยแพร่ และให้บริการสารสนเทศดิจิทัลภายในสถาบัน 3) มีบุคลากรรับผิดชอบด้านเทคนิคและด้านเนื้อหา 4) มีการจัดสรรงบประมาณจากสถาบัน 5) ทรัพยากรสารสนเทศดิจิทัลที่นำมาดำเนินการ ได้แก่ รายงานการวิจัย บทความวิจัย และบทความวิชาการ 6) อุปกรณ์เทคโนโลยีประกอบด้วยฮาร์ดแวร์และซอฟต์แวร์ ซึ่งมีสมรรถนะปานกลาง และมีปริมาณเพียงพอ 7) มีการดำเนินการตามมาตรฐานข้อมูลและมาตรฐานการทำงาน 8) มีความร่วมมือกันทั้งภายในสถาบัน ความร่วมมือระหว่างสถาบัน และความร่วมมือกับภาคเอกชน ส่วนด้านปัญหาและความต้องการ ผลการวิจัยนำเสนอสอดคล้องกัน โดยพบว่ายังประสบปัญหาขาดนโยบายและบุคลากรรับผิดชอบที่ชัดเจน ขาดการประสานงานระหว่างหน่วยงานที่รับผิดชอบ ขาดงบประมาณและความพร้อมด้านเครื่องมือและอุปกรณ์เทคโนโลยี รวมถึงบุคลากรที่เชี่ยวชาญเฉพาะด้าน จึงควรมีแผนแม่บทในการบริหารจัดการทรัพยากรสารสนเทศดิจิทัลของสถาบันอย่างชัดเจน ควรมีหน่วยงานกลางประสานงานกับหน่วยงานภายในสถาบัน ควรมีการวางแผนด้านงบประมาณ และการเตรียมพร้อมด้านเครื่องมือและอุปกรณ์เทคโนโลยี ควรมีระบบฐานข้อมูลกลางที่เข้าถึงได้สะดวก และมีการพัฒนาความเชี่ยวชาญของบุคลากร รวมถึง ควรมีการร่วมมือกันระหว่างบุคลากรผู้ปฏิบัติงานในแต่ละหน่วยงานที่เกี่ยวข้อง The research objectives were 1) management state of digital copyrighted materials 2) the problem and need on management of digital copyrighted materials in Thai Higher Educational Institutes (THEs). The research tool was Semi-structured interview. The respondents were 7 higher administrators and 16 operating staff. The result of the study indicated the management state of digital copyrighted materials in 8 issues 1) has no vivid policy and no strategic planning about digital copyrighted materials management 2) the library of institute is division has direct responsibility in digital copyrighted materials such as production, distribution and service 3) the operating staff are 2 groups ; technical specialist and content specialist who come from several divisions 4) the scholarly materials that was digitized were academic articles, research articles and research reports 5) supporting budget were allocated by administrators 6) equipment and infrastructure contain hardware and software which are medium capacity and adequate quantity 7) standard of information operated in both information standard and work processing standard 8) cooperation have 3 levels; cooperate among divisions in campus, cooperate with other institutes, and cooperate with private sectors. The result of problem and need on digital copyrighted materials management were found that THEs has no clear policy about it, problem on direct responsibility and coordination of staff, equipment and infrastructure are inadequate, inadequacy of budget and technical specialist. The institutes should have master plan provide the division responsible in digital materials management, have central division of institutes operate for coordination among related division, have central database system collected digital academic works, have plan of budget and investment in materials, have plan of personal competency, and should have cooperation between staff in institutes.